PENGARUH LAMA WAKTU THAWING TERHADAP KUALITAS SEMEN KERBAU LUMPUR (Bubalus bubalis): THE EFFECT OF THAWING TIME ON THE QUALITY OF MUD BUFFALO SEMEN (Bubalus bubalis) - Windi Yolanda; Rini Elisia; Maiyontoni; Refika Komala (Tropical Animal Science, 2026)
Artificial insemination (AI) in buffaloes in Indonesia still faces challenges, one of which is the low quality of frozen semen due to improper thawing processes. Buffalo semen has physiological advantages, but it is also more susceptible to damage during thawing and cryopreservation processes. Previous studies have shown that thawing time affects sperm motility. This study aims to determine the effect of thawing time on buffalo semen quality in order to improve AI success rates. This study used 20 straws of frozen buffalo semen with an experimental research method and data analysis using RAK, consisting of 4 treatments (P1: 30 seconds, P2: 60 seconds, P3: 90 seconds, P4: 120 seconds) and 5 replicates. The observation parameters were PTM (Post Thawing Motility), viability, abnormality, MPU (Membrane Plasma Integrity), and TAU (Acrosome Cap Integrity). The results showed that the mean values of PTM, viability, abnormality, MPU, and TAU of the four treatments were not significantly different (P>0.05). These results indicate that thawing frozen buffalo semen for up to 120 seconds (2 minutes) at a temperature of 370? can still maintain the viability, abnormalities, MPU count, and TAU count of buffalo sperm before insemination. There is a tendency for the PTM and MPU counts in the 120-second thawing treatment to be higher than in the other treatments. Based on the research results, it can be concluded that thawing for 30 seconds, 60 seconds, 90 seconds, and 120 seconds did not produce significant differences in PTM, viability, abnormalities, MPU, and TAU of frozen buffalo semen, so thawing up to 120 seconds can still be done.